Avaliação do potencial como biomaterial de hidrogéis de N-carboxietil quitosana e goma alfarroba oxidada - Araujo, Luis Felipe Santos (2022)
Injectable hydrogels are a category of gels in which the precursors are applied directly to the desired site, where cross-linking occurs, with the aim of restoring injured tissue. Natural polymers are indicated for their synthesis because they present structures that resemble the extracellular matrix. Chitosan is a water-insoluble semi-synthetic polysaccharide, however its solubility can be increased with structural modifications, such as the insertion of the carboxyethyl group in its chain through the Michael addition reaction with acrylic acid. Locust bean gum is a galactomannan from the endosperm of Ceratonia siliqua seeds that has vicinal diols that can be oxidized via reaction with sodium periodate. This reaction produces a polyaldehyde that can bind to the amine groups of chitosan through the Schiff base reaction, resulting in cross-linking and hydrogel formation. This work proposes the preparation of injectable hydrogels formed by N-carboxyethyl chitosan (NCEQ) and oxidized locust bean gum (GAO). Locust bean gum was oxidized in three different theoretical oxidation degrees (10, 30 and 50%), which were characterized by FTIR, GPC and 1H NMR. A band at 1728 cm-1 (ν C=O) in the FTIR spectrum confirmed the formation of aldehyde groups in the oxidized derivatives. The oxidation reaction resulted in a peak molar mass reduction of 86.3, 97.7 and 99.1% for oxidized gums 10, 30 and 50% respectively. This indicates that the reaction is accompanied by a degradation in the polymer chain. New peaks between 5.7 and 4.1 ppm were observed in the 1H NMR spectrum, which are attributed to the formation of hemiacetal structures. The NCEQ formation reaction was confirmed by the increase in the relative intensity of the band at 1572 cm-1 and the appearance of the band at 1407 cm-1 in the spectrum of the infrared region. The NCEQ/GAO hydrogels (w/w ratio 1:1) presented gelation times between 17 and 37 s, swelling capacity between 109 and 399% in water and up to 10% in phosphate buffer, and porosity values ranging from 37 to 76%. It was observed that the porosity increases with the degree of oxidation of GAO. Hydrogels had a mass loss of between 27.8 and 35.3% after 28 days in in vitro degradation, with the loss increasing with a lower degree of oxidation. Hydrogels are viable for cell growth. The results indicate potential application of the materials as injectable hydrogels.